2023
DOI: 10.7759/cureus.33339
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Sublingual Misoprostol Versus Intramuscular Oxytocin in the Active Management of Third Stage of Labor

Abstract: Misoprostol has attracted low-income low-resource countries for the active management of the third stage of labor. The objective of this study was to compare the efficacy of sublingual misoprostol and intramuscular oxytocin in the active management of the third stage of labor. Study designThis was a prospective randomized controlled trial in which a total of 407 healthy pregnant women having singleton pregnancy, cephalic presentation, and normal vaginal delivery were divided into two groups. In the first group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…However, in contrast to our findings, studies by Pangeni et al [14] and Abd Allah et al [15] did not show a significant difference in mean blood loss after delivery between the two drugs. Conversely, Mishra et al [16] found a significantly higher blood loss and PPH incidence in the misoprostol group than in the oxytocin group. The varying results recorded among studies could be due to differences in the methodology including the type of blinding used, the sample size, and the quality of the uterotonic agents employed [17,18].…”
Section: Discussionmentioning
confidence: 89%
“…However, in contrast to our findings, studies by Pangeni et al [14] and Abd Allah et al [15] did not show a significant difference in mean blood loss after delivery between the two drugs. Conversely, Mishra et al [16] found a significantly higher blood loss and PPH incidence in the misoprostol group than in the oxytocin group. The varying results recorded among studies could be due to differences in the methodology including the type of blinding used, the sample size, and the quality of the uterotonic agents employed [17,18].…”
Section: Discussionmentioning
confidence: 89%